2017
DOI: 10.1038/ncomms15558
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function CHCHD10 mutations in cytoplasmic TDP-43 accumulation and synaptic integrity

Abstract: Although multiple CHCHD10 mutations are associated with the spectrum of familial and sporadic frontotemporal dementia–amyotrophic lateral sclerosis (FTD–ALS) diseases, neither the normal function of endogenous CHCHD10 nor its role in the pathological milieu (that is, TDP-43 pathology) of FTD/ALS have been investigated. In this study, we made a series of observations utilizing Caenorhabditis elegans models, mammalian cell lines, primary neurons and mouse brains, demonstrating that CHCHD10 normally exerts a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(155 citation statements)
references
References 45 publications
(99 reference statements)
8
145
2
Order By: Relevance
“…Even stronger clustering was observed for G66V and E127K in nearly all cells. Other variants in the hydrophobic domain had little (G58R and G66S) or no effect (V57E) on CHCHD10 localization but may have subtle effects on mitochondrial morphology similar to reports for S59L (Bannwarth et al , ; Woo et al , ). The other variants showed no gross abnormalities in expression level and localization by immunofluorescence (Fig EV3), highlighting the importance of the hydrophobic region and the CHCH domain.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Even stronger clustering was observed for G66V and E127K in nearly all cells. Other variants in the hydrophobic domain had little (G58R and G66S) or no effect (V57E) on CHCHD10 localization but may have subtle effects on mitochondrial morphology similar to reports for S59L (Bannwarth et al , ; Woo et al , ). The other variants showed no gross abnormalities in expression level and localization by immunofluorescence (Fig EV3), highlighting the importance of the hydrophobic region and the CHCH domain.…”
Section: Resultssupporting
confidence: 74%
“…Patient fibroblasts with the S59L mutation show an altered mitochondrial network structure, but as mitochondrial fusion is normal, this may be secondary to instability of mitochondrial DNA (Bannwarth et al , ). Overexpression of human wild‐type but not R15L or S59L CHCHD10 rescues the shorter lifespan of Caenorhabditis elegans lacking the CHCHD10 homolog har‐1 (Woo et al , ). The reported inhibition of apoptosis by CHCHD10 S59L (Genin et al , ) has not been replicated by others (Woo et al , ) and is difficult to reconcile with a neurodegenerative process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus CHCHD10 colocalizes with DAPI as suggested by a positive Pearson correlation coefficient. A recent study also showed nuclear localization (21). We further validated the nuclear signal by use of a stable knockdown of CHCHD10 in HEK293 cells (Fig.…”
Section: Chchd10 Is a Hypoxia-sensitive Genementioning
confidence: 87%
“…Thus, even in the presence of elevated levels of MNRR1 the two mutant versions of CHCHD10 prevent phosphorylation of MNRR1, giving rise to the mitochondrial phenotype seen. A recent study also showed that CHCHD10 is localized to both the mitochondria and the nucleus and that its normal function prevents the neurotoxic mitochondrial localization of the protein TDP-43 whereas two other disease associated mutations, R15L and S59L, promote its cytoplasmic mislocalization (21). These mutations have also been shown to accumulate excessive mitochondrial iron (37).…”
Section: Discussionmentioning
confidence: 99%